The association between pain and impulse control behaviours in Parkinson's disease. (September 2020) - Kobylecki, Christopher; Carrasco, Roberto; Boca, Mihaela; Lawton, Michael; Chaudhuri, K. Ray; Hu, Michele T.; Grosset, Donald G.; Silverdale, Monty A.
Highlights: Impulse control behaviors (ICB) and pain in Parkinson's disease share potential common substrates. We studied the relationship between pain and ICB in 1909 participants with Parkinson's disease. People with a history of ICB scored higher on pain scales and were more likely to have neuropathic pain. After adjusting for age, dopamine agonist use, and mood symptoms, people with ICB were more likely to experience high pain. These results indicate a potential mechanistic link between pain and impulsive behaviour.